Rethinking the Tunisian miracle: a party politics view. Issue 5 (4th July 2018) - Yardımcı-Geyikçi, Şebnem; Tür, Özlem
ABSTRACT: Five years on from the Tunisian revolution, Tunisia stands as the sole success story of the Arab Spring. The country since then has managed to adopt a pluralist and democratic constitution, and held three free and fair elections. Accordingly, in the eyes of several observers, Tunisia is now in the process of consolidating its new democracy. However, the reality on the ground seems much gloomier, as most recent opinion surveys suggest that there is a significant degree of dissatisfaction, not only with political parties and Parliament but also with the very institution of democracy. Nevertheless, what accounts for this change? After the collapse of the long-lasting and oppressive Ben Ali regime, how, just in five years, has Tunisians' confidence in the democratic process changed? This article accounts for this state of affairs from a party politics view, arguing that political parties, which are the main protagonists of the consolidation process, fail to fulfill their role of acquiring legitimacy for the new regime. While party–state relations seem to be stabilized due to the inclusiveness of the constitution-making process, both inter-party relationships and the relationship between parties and society suffer from numerous flaws which, in turn, hamper the democratic consolidation process.